Effect on Mechanical Properties of Heat Treated High Manganese Austenitic Cast Iron - Muzafar, A. K.; Rashidi, M. M.; Mahadzir, Ishak; Shayfull, Z. (EDP Sciences, 2016)
This work presents an attempt to study the effect of manganese addition and heat treatment on higher carbon austenitic cast iron to form high manganese austenitic cast iron with reduced nickel content (Mn-Ni-resist) on mechanical properties. The combination on microstructure (microsegregation), mechanical properties and the relationship of heat treatment on the alloy were analyzed. For this purpose Mn-Ni-resist (4.50C, 2.64Si, 6.0 Mn, 10 Ni) was melted and cast in the form of Y-block test pieces. Four different heat treatment procedures were applied to the as-cast to investigate the effect of alloy modifications on Mn-Ni-resist. Optical and scanning electron microscopies were used for microstructure investigation. To determine the mechanical properties tensile test and hardness test were carried out. The result indicates both composition and heat treatment affect the performance of Mn-Ni-resist intensively. Microprobe analysis shows some silicon segregation near the graphite and practically little segregation of manganese. The increase in manganese contents developed some fractions of segregated carbide structures in LTF region located at austenite eutectic cell frame, which caused the tensile properties to drop in a small range. Application of annealing heat treatment gradually changed the carbide formation, so is the material’s strength.